Pengaruh Infrastruktur, Sektor Pariwisata, Tenaga Kerja dan Pdrb Terhadap Pendapatan Asli Daerah Kabupaten/Kota Di Provinsi Jambi - Neli Mariana Manihuruk; Zulfanetti; Rosmeli (JOURNAL OF SHARIA ECONOMICS, 2026)
This study aims to analyze the effect of road length, tourism visits, labor, and Gross Regional Domestic Product (GRDP) on Regional Original Revenue (PAD) of regencies/cities in Jambi Province during the 2015–2024 period. The data used are secondary data obtained from the Central Statistics Agency (BPS) of Jambi Province and related institutions. This study employs panel data regression analysis using the Fixed Effect Model (FEM) approach. Model selection was conducted through the Chow Test and Hausman Test, which indicated that FEM was the most appropriate model for this study.The results show that simultaneously, road length, tourism visits, labor, and GRDP significantly affect PAD in regencies/cities of Jambi Province. Partially, labor and GRDP have a positive and significant effect on PAD, while road length and tourism visits do not have a significant effect on PAD. The labor variable has a coefficient of 166,489.08 with a probability value of 0.0268, while the GRDP variable has a coefficient of 0.0048 with a probability value of 0.0014. Meanwhile, road length and tourism visits have probability values of 0.8165 and 0.6655 respectively, which are higher than the 5 percent significance level. The Adjusted R-Squared value of 0.926 indicates that the independent variables explain 92.6 percent of the variation in PAD.The findings indicate that regional economic activity and labor absorption are the main factors influencing the increase of PAD in Jambi Province. Therefore, local governments need to encourage productive economic growth, improve labor quality, optimize investment, and strengthen regional fiscal governance in order to enhance sustainable regional financial independence.